PROPOSTA DE MODELO DE CADEIA DE VALOR PARA UM CENTRO UNIVERSITÁRIO - Samuel Martim de Conto (Universidade Federal de Santa Catarina, 2013)
Competition is present in all markets and it has also been especially present in Higher Education lately. Professionalization and management competence in Higher Education Institutions (IES) are essential in order to assess competitive advantage facing other organizations. The Value Chain Model originally proposed by Porter (1989) is a structure composed by two assemblies of activities which, when integrated, enables the organization improvement. The complexity of operational activities of an Educational Institution, which intensively develops qualified workforce, contributes for the reflection on the models and structures that may help on qualified education development. For the current study, exploratory and qualitative approach was carried out as well as technical procedures of secondary source and bibliographical data about the subject. A Value Chain Model for a Higher Education Institution is proposed as a result.